Structural basis of aggregate binding by the AAA+ disaggregase ClpG - Katikaridis, Panagiotis; Simon, Bernd; Jenne, Timo; Moon, Seongjoon; Lee, Changhan; Hennig, Janosch; Mogk, Axel (Journal of Biological Chemistry, 2023)
Severe heat stress causes massive loss of essential proteins by aggregation, necessitating a cellular activity that rescues aggregated proteins. This activity is executed by ATP-dependent, ring-forming, hexameric AAA+ disaggregases. Little is known about the recognition principles of stress-induced protein aggregates. How can disaggregases specifically target aggregated proteins, while avoiding binding to soluble non-native proteins? Here, we determined by NMR spectroscopy the core structure of the aggregate-targeting N1 domain of the bacterial AAA+ disaggregase ClpG, which confers extreme heat resistance to bacteria. N1 harbors a Zn2+-coordination site that is crucial for structural integrity and disaggregase functionality. We found that conserved hydrophobic N1 residues located on a β-strand are crucial for aggregate targeting and disaggregation activity. Analysis of mixed hexamers consisting of full-length and N1-truncated subunits revealed that a minimal number of four N1 domains must be present in a AAA+ ring for high-disaggregation activity. We suggest that multiple N1 domains increase substrate affinity through avidity effects. These findings define the recognition principle of a protein aggregate by a disaggregase, involving simultaneous contacts with multiple hydrophobic substrate patches located in close vicinity on an aggregate surface. This binding mode ensures selectivity for aggregated proteins while sparing soluble, non-native protein structures from disaggregase activity.
Keywords: 70 kda heat shock protein (hsp70); Aggregated protein; Atpase associated with diverse cellular activity (AAA); ATPases; Cellular activities; Heat shock protein; Molecular chaperones; Non-native; Protein aggregates; Protein aggregation; 70 kDa heat shock protein (Hsp70); ATPase associated with diverse cellular activities (AAA); molecular chaperone; protein aggregation; stress